Malignant hyperthermia when dantrolene is not readily available - Gong, Xiaodan (BMC anesthesiology, 2021)
Malignant hyperthermia is a rare but life-threatening pharmacogenetic muscle disorder characterized by abnormal hypermetabolic reactions and commonly triggered in susceptible individuals by volatile anesthetics or succinylcholine, or both. Unfortunately, the specific medicine dantrolene is not readily available in many countries including China. The aim of this study was to find the characteristics of malignant hyperthermia under the situation that dantrolene is not readily available. The cases of malignant hyperthermia reported on the most commonly used databases in China from 1985 to 2020 were analyzed. The inclusion criteria were the MH episodes only related to anesthesia. The exclusion criteria were dubious MH episodes only caused by Ketamine administration or MH episodes irrelevant to anesthesia. Independent samples t-test and Pearson's chi-squared test were applied to assess the difference between the survived and death cases. Ninety-two cases of malignant hyperthermia reported on the most commonly used databases in China from 1985 to 2020 were analyzed. Median (IQR [range]) age was 18.5 (11.8-37.0 [0-70.0]) years. Compared with the survived cases, the death cases had higher maximum end-tidal partial pressure of CO (P = 0.033), the maximum arterial partial pressure of CO2 (P = 0.006), temperature first measured when the patient was first discovered abnormal (P = 0.012), and maximum temperature (P < 0.001). Besides, the death cases had less minimum pH (P < 0.001) and higher potassium (P < 0.001) and were more likely to have coagulation disorders (p = 0.018). Concerning treatment, cases used furosemide (P = 0.024), mannitol (P = 0.029), blood purification treatment (P = 0.017) had the advantage on the outcome. Creatine phosphokinase, myoglobin, and MB isoenzyme of creatine phosphokinase differed greatly among cases during the first week. 43 (46.7%) cases had congenital diseases. 12 (13.0%) cases were reported with abnormal laboratory test results or abnormal signs that are possibly relevant before anesthesia. In countries that dantrolene is not readily available, early warning, diagnosis, and prompt effective therapies are crucial for MH patients to survive.